The Taste of Language and Home - Jungblut, Jamie (Satura, 2024)
I feed on language. Early on, I grew fascinated with the different sensations words create, when they roll off my tongue or onto paper. I adored the diversity of effects I could achieve with every bite full of meaning. But it was not until later that I realized how different every language tastes. It was only logical that, after this discovery, I developed a new hunger. A hunger, somewhat less urgent than that for food, community, or intimacy, but present without pause.